Assessment and evaluation of football performance - Rosch, D.; Hodgson, R.; Peterson, T. L.; Graf-Baumann, T.; Junge, A.; Chomiak, J.; Dvorak, J. (The American Journal of Sports Medicine, 2000)
The most important variables for measuring performance in team sports such as football are physical condition and technical and tactical performance. However, because of the complexity of the game of football it is difficult to ascertain the relative importance of each of these variables. The aim of the present study was to develop a standardized test battery to evaluate physical performance in football players. The F-MARC test battery was designed to closely relate to the football player's normal activity and comprised a functional, structured training session of approximately 2.5 hours. It included a "quality rating" of the warm-up procedure, tests of flexibility, football skills, power, speed, and endurance. The players finished with a cool-down. A total of 588 football players underwent the F-MARC test battery. Mean values for performance on each test are presented for groups of differing age and skill levels. The test battery proved to be a feasible instrument to assess both physical performance and football skills. This study supports the proposal by Balsom (1994) that analysis of an individual player's physical profile, in relation to mean values for a similar age group and skill level, might be of assistance to the coach in objectively evaluating the effects of a specific training program. It may also be of use to the physician and physical therapist responsible for monitoring progress during rehabilitation after football injuries.